Acute decrease in plasma testosterone and appetite after either glucose or protein beverages in adolescent males. (16th May 2019) - Schwartz, Alexander; Hunschede, Sascha; Lacombe, Russel John Scott; Chatterjee, Diptendu; Sánchez‐Hernández, Diana; Kubant, Ruslan; Bazinet, Richard Paul; Hamilton, Jill K.; Anderson, Gerald Harvey
Abstract: Objective: Chronic testosterone blood concentrations associate with food intake (FI), but acute effects of testosterone on appetite and effect of protein and glucose consumption on testosterone response have had little examination. Methods: In a randomized, crossover study, twenty‐three adolescent (12‐18 years old) males were given beverages containing either: (a) whey protein (1 g/kg body weight), (b) glucose (1 g/kg body weight) or (c) a calorie‐free control (C). Plasma testosterone, luteinizing hormone (LH), GLP‐1 (active), ghrelin (acylated), glucose, insulin and subjective appetite were measured prior (0) and at 20, 35 and 65 minutes after the consumption of the beverage. FI at an ad libitum pizza meal was assessed at 85 minutes. Results: Testosterone decreased acutely to 20 minutes after both protein and glucose with the decrease continuing after protein but not glucose to 65 minutes ( P = 0.0382). LH was also decreased by both protein and glucose, but glucose had no effect at 20 minutes in contrast to protein ( P < 0.001). Plasma testosterone concentration correlated positively with LH ( r = 0.58762, P < 0.0001) and negatively with GLP‐1 ( r = −0.50656, P = 0.0003). No associations with appetite, ghrelin or glycaemic markers were found. Food intake was not affected by treatments. Conclusion: Protein or glucose ingestion results in acute decreases in both plasma testosterone and LH in adolescent males. The physiological significance of this response remains to be determined as no support for testosterone's role in acute regulation of food intake was found.